THE INFLUENCE OF BAG QUALITY PERCEPTION, BRAND IMAGE, PRICE PERCEPTION AND PROMOTION ON PURCHASE DECISIONS - Nur Abwaini Nasution; Eka Dewi Setia Tarigan; Khairunnisak Khairunnisak; Hesti Sabrina (SEAN Institute, 2023)
the purpose of this study was to determine and analyze the effect of perceived quality, brand image, price perception and promotion on purchasing decisions on Oppo smartphone users in Billah Hilir District, Labuhanbatu Regency, North Sumatra. The population in this study were all Oppo smartphone users in the District of Bilah Hilir, Labuhanbatu Regency, North Sumatra and the sample from the study were people who bought Oppo smartphones directly at 12 smartphone counters in Bilah Hilir District, Labuhanbatu Regency, North Sumatra. The technique used in the sampling of this research is by using a purposive sampling technique. The analytical tool used is multiple linear regression analysis because more than one independent variable is used with the SPSS program. Based on the results of the analysis that has been carried out, it shows that perceived quality, brand image,